Assisting School Teachers in Developing and Implementing Learning Modules Infused with Computational Thinking Principles - Harjanto, Ignatius; Teopilus, Susana; Anggraini, Kristin (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This community service activity program aims to guide school teachers to infuse CT principles into the learning modules and to implement their CT-infused modules in their classes. The methods for implementing community service activities were workshops and mentoring activities. The target of the activity was pre-school, elementary, and junior-high school teachers at School Foundation of Yohanes Gabriel sub-District Tuban. The instruments used to collect data were a survey, observation sheets, and learning-module documents. The data were analyzed to describe the teachers’ abilities to create CT-infused modules and their skills to carry out these modules in their instructional practices. The results of this program showed that the teachers understood CT principles and taxonomy and could create appropriate teaching modules infused with CT principles. It implies that this community service program could improve teachers’ teaching skills through their efforts to integrate computational thinking into their instructional practices.